Evolution and treatment of idiopathic pulmonary fibrosis - Torrisi, Sebastiano Emanuele; Kahn, Nicolas; Kreuter, Michael (La presse médicale & Quarterly medical review, 2020)
Idiopathic pulmonary fibrosis (IPF) is a chronic and devastating disease of unknown etiology, characterized by irreversible morphological changes, ultimately leading to lung fibrosis and death. In recent years, significant progress has been achieved in understanding the pathogenesis of IPF. Moreover, we assisted to the conceptual change of the pathogenic hypothesis that currently considers IPF as a primarily fibrotic driven disease. However, despite the undeniable progress, the diagnosis of IPF remains still very complex requiring the presence of a team of experts to achieve the highest level of diagnostic confidence. The advent of antifibrotics has radically changed the treatment landscape of IPF and new promising drugs are currently under evaluation. Furthermore, a more extensive use of non-pharmacological treatments has also to be encouraged in all patients both to reduce symptoms and improve quality of life.